Postural status of preschool children in Novi Sad - Romanov Romana; Stupar Dušan; Međedović Bojan; Brkin Dejan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2014)
A survey was conducted in Novi Sad in the preschool institutions of 'Radosno detinjstvo' on a sample of 423 preschool children of both sexes, ages 6 and 7. The subject of this paper are postural disorders on the spinal column in the sagittal and frontal planes, as well as foot deformities. The aim of the research is to determine the frequency of disorder of postural status of the spine (kyphosis, lordosis and scoliosis) and deviation from the normal status of the foot, and the analysis of the differences between boys and girls. Assessment of the postural status of the feet was performed by means of using the Pedikom computer system for digital computerised pedography. Assessment of spine postural status was done by means of SpineScan portable device. Data were analysed according to the frequency for the assessment of spinal status, the status of the foot, all according gender. Significance of the gender-conditioned differences was determined by the Chi-square test. The results indicate that in the examined population, the most common posture is lordotic bad posture, 41.31% with male examinees and 36.66% with female examinees. A statistically significant difference in relation to sexual dimorphism was found for the parameter of scoliotic bad posture (Sig. = 0.008). In terms of deviation from the normal status of the feet, in the examined population, pronating foot level I accounts for 43.23%, pronating foot level II accounts for 16.66% and high-arched foot accounts for 10.16%. Quantitative results indicate the need for corrective gymnastic to correct but also prevent postural deformities by introducing of the same as an everyday directed activity of preschool population.